2001
DOI: 10.2307/1352818
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Ecology of 0-Group Sea Bass, Dicentrarchus labrax, in Salt Marshes of Mont Saint Michel Bay (France)

Abstract: 0-group sea bass, Dicentrarchus labrax, colonize intertidal marsh creeks of Mont Saint Michel Bay, France, on spring tides (e.g., 43% of the tides) during flood and return to coastal waters during ebb. Most arrived with empty stomachs (33%), and feed actively during their short stay in the creeks (from 1 to 2 h) where they consumed on average a minimum of 8% of their body weight. During flood tide, diet was dominated by mysids, Neomysis integer, which feed on marsh detritus. During ebb, when young sea bass lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
85
3
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 53 publications
(64 reference statements)
9
85
3
1
Order By: Relevance
“…Since the introduction of the outwelling concept (Odum, 1968), which states that tidal events export detrital organic matter produced in salt marshes to marine waters, strong evidence has also indicated that the export of organic matter from terrestrial to aquatic systems supports secondary production (Loneragan et al, 1997;Kurata et al, 2001). Consequently, salt marshes generally have a very high conservation value, directly as a result of their species complement and because of their role as a feeding ground for migrant birds (Norris et al, 1997;Lefeuvre et al, 2000), and fish, especially juveniles (Boesch and Turner, 1984;Laffaille et al, 2001Laffaille et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the introduction of the outwelling concept (Odum, 1968), which states that tidal events export detrital organic matter produced in salt marshes to marine waters, strong evidence has also indicated that the export of organic matter from terrestrial to aquatic systems supports secondary production (Loneragan et al, 1997;Kurata et al, 2001). Consequently, salt marshes generally have a very high conservation value, directly as a result of their species complement and because of their role as a feeding ground for migrant birds (Norris et al, 1997;Lefeuvre et al, 2000), and fish, especially juveniles (Boesch and Turner, 1984;Laffaille et al, 2001Laffaille et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…During high tide, young sea bass (Dicentrarchus labrax L.) and sand gobies (Pomatoschistus minutus Pallas) exploit salt marsh production by feeding on resident invertebrates, mainly Orchestia gammarella (Laffaille et al, 1999(Laffaille et al, , 2001. Pomatoschistus minutus is among the most abundant fish species of coastal waters of western Europe (Costa and Cabral, 1999), and occurs frequently at high densities in a large European intertidal salt marsh (Laffaille et al, 2000a;Salgado et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top piscivorous predator (Kottelat, 2008), it exploits both coastal and shallow waters (Pickett and Pawson, 1996;Sanchez Vazquez and Munoz-Cueto, 2014) and for this reason is usually described as euryhaline fish species. Each year, young seabass colonise supratidal and intertidal marsh creeks and subtidal and intertidal flats to feed (Laffaille et al, 2001a). Grey mullets, although less abundant in estuaries (Nicolas et al, 2010), also have a key role and are described as marine seasonal migrants.…”
mentioning
confidence: 99%
“…about 6 h), which is a common pattern for thicklip mullet (Chelon labrosus) and European seabass (Dicentrarchus labrax ) individuals in northwestern European coastal actchements (Laffaille et al, 2001a). The variability in responses of both fish species' metabolism to short-term salinity variations at different temperatures was compared.…”
mentioning
confidence: 99%